Epidemiology of marine turtle fibropapillomatosis and tumour-associated chelonid alphaherpesvirus 5 (ChHV5; Scutavirus chelonidalpha5) in North-Western Mexico: a scoping review implementing the one health approach - Joelly Espinoza; Alonzo Alfaro-Núñez; Carlos Cedillo-Peláez; Helena Fernández-Sanz; Agnese Mancini; Alan A. Zavala-Norzagaray; Cesar Paul Ley-Quiñonez; Erika Santacruz López; Miguel Angel Garcia-Bereguiain; A. Alonso Aguirre; Eduardo Reséndiz (Veterinary Research Communications, 2024)
Fibropapillomatosis (FP) - tumour-associated chelonid alphaherpesvirus 5 (ChHV5; Scutavirus chelonidalpha5) - is a disease that affect marine turtles around the world, and characterized by the formation of cutaneous tumours that can appear anywhere on the body. We carried out a thorough literature search (from 1990 to 2024) in the feeding sites of North-western Mexico, a region that hosts important habitats for feeding, development, and reproduction for five of the seven existing sea turtle species. We found 18 reports recording a total of 32 cases of FP and/or ChHV5/Scutavirus chelonidalpha5 in coastal and insular areas of North-western Mexico. Baja California Sur resulted with the highest number of cases (75%). While the first case of ChHV5/Scutavirus chelonidalpha5 infection was reported in 2004, the presence of FP tumours was reported in 2014 and became more frequent between 2019 and 2024. The affected species were black, Chelonia mydas (50%), olive ridley, Lepidochelys olivacea (46.8%) and loggerhead turtles, Caretta caretta (3.2%). Tumours occurred mainly in anterior flippers (46.1%) and neck (22.5%), and most had a nodular and verrucous appearance with a rough surface. In the study region, there is a potential sign of the emergence of the ChHV5/Scutavirus chelonidalpha5 infections and FP disease during the last 20 years, with a rapid increase during the last 10 years. As long as infections by ChHV5/Scutavirus chelonidalpha5 and the prevalence of the FP disease may be potentially influenced by anthropogenic activities, a One Health approach is needed to understand and improve sea turtles’ health.